DINAMIKA HUBUNGAN MUHAMMADIYAH DAN PARTAI POLITIK DI INDONESIA - Ahmad Sholikin (Universitas 17 Agustus 1945 Jakarta, 2020)
Muhammadiyah's contact with political parties in actualizing their ideas and ideals will be discussed in this chapter. Muhammadiyah's involvement with political parties from the pre-independence era until now is divided into 4 patterns of relations. If it is analogous to Muhammadiyah's relationship with a Political Party like a marriage, there will be four